The Role of Competencies and Education in Increasing Entrepreneurial Intention in Creative Economy - Sandroto, Christine Winstinindah; Ramawati, Yussi; Darmoyo, Syarief (Universitas Prasetiya Mulya, 2018)
The creative economy is being increasingly encouraged by the Indonesian government, the existing entrepreneurs are mostly engaged in the culinary industry. This study aims to describe the role of competencies and education in increasing entrepreneurial intention in the creative economy. Three hundred and five questionnaires were distributed to creative entrepreneurs, consisting of 162 respondents in Jakarta and 143 in Balikpapan using convenience sampling. Research findings show that there is no difference between the mean scores of entrepreneurial competencies in Jakarta and Balikpapan. Furthermore, the level of education has a positive effect on (i) entrepreneurial intention, (ii) entrepreneurial professional attraction, and (iii) entrepreneurial networking support. There is a positive relationship between education level and monthly revenue, as well as between entrepreneurial competencies and monthly revenue. The findings of this research would suggest government and education institution to further develop entrepreneurship education and train them with various methods and to cultivate interests in other creative sub-sectors.